Fishermen Empowerment Through Product Diversification Viewed from the Maqashid Syariah Perspective in Pantai Labu District - Sari, Riski Ardila; Harahap, Rahmat Daim; Jannah, Nurul (Universitas Muhammadiyah Jakarta, 2024)
Economic empowerment is one way to change people's lives for the better. Pantai Labu sub-district is known as a coastal area that has the potential for abundant marine catches. This study aims to evaluate the effectiveness of the product diversification-based fishermen empowerment program by using the maqashid sharia perspective as an analytical framework. This research was conducted in three fishing villages in Pantai Labu Sub-district, by identifying the potential product diversification that can be produced from marine products. The research method used was a qualitative case study with a descriptive analysis approach. Data collection was carried out through in-depth direct interviews. The results show that product diversification such as seafood processing and home industry development has had a positive impact on the income and food security of fishing communities. In addition, this empowerment also encourages the achievement of Maqasyid Sharia objectives, such as increased income that safeguards wealth (al-mal), increased skills that support the intellect (al-aql), and family welfare that supports offspring (an-nasl). However, despite its great potential, product diversification often faces various challenges in business development, such as capital constraints, limited market access, and lack of product innovation